Impaired Expression of Glycogen Synthase mRNA in Skeletal Muscle of NIDDM Patients - Vestergaard, Henrik; Bjørbæk, Christian; Andersen, Per H; Bak, Jens F; Pedersen, Oluf (Diabetes (New York, N.Y.), 1991)
Based on recent studies of the abnormal physiology and biochemistry of the glycogen synthesis in skeletal muscle of non-insulin-dependent diabetes mellitus (NIDDM) patients and their first-degree relatives, the key enzyme of this pathway, glycogen synthase (GS), is considered a candidate gene in the pathogenesis of insulin resistance. Comparing matched groups of 14 NIDDM patients with 14 control subjects, we found that impaired insulin-stimulated nonoxidative glucose metabolism of peripheral tissue (P < 0.02) and reduced total GS activity (P < 0.05) of vastus lateralis muscle from patients with NIDDM were accompanied by a 39% reduction (P < 0.02) in the steady state level of GS mRNA per microgram DNA of muscle. In both diabetic and control subjects, the mRNA expression of GS was unaffected after euglycemic-hyperinsulinemic clamp for 4 h. With single-stranded conformation polymorphism analysis of the entire coding sequence of the GS gene, we were unable to detect any genetic variants in a subset of eight NIDDM patients. We conclude that abnormal pretranslational regulation of the GS gene may contribute to impaired glycogen synthesis of muscle in NIDDM. Our studies give no evidence for structural changes in the coding region of the GS gene, and it is unknown if the decreased mRNA expression is due to impaired transcription or accelerated degradation of the transcript.